The Italian Political Science community, 2002-2022 - Bruno Marino (Italian Political Science, 2023)
What has been the evolution of the Italian Political Science community in the past 20 years? Have there been relevant differences from the career level, geographical, or gender-related viewpoints? This article aims at answering these questions, which are even more interesting on the eve of the start of a new career path for Italian academics, which should markedly modify especially the early stages of career. After discussing the numerical growth of Italian Political Science from 2002 until 2022, the article explores the differences related to career levels and geography. On the former point, there has been an increase in the importance of Associate Professors but also Non-tenure-track academics. In this regard, if the trend experienced in 2018-2022 continued in the following years, we would face a situation where the relative majority of political scientists do not hold a tenure-track position. On the latter aspect, universities located in Northern regions continue employing a relevant sector of the Italian Political Science community, with Central and, especially, Southern universities having a much more marginal role. Finally, the article explores gender-related differences. While there are noticeable signs of a growing prominence of women from the numerical and the growth rate viewpoints, opposite indicators point to a marked difficulty of women to climb the academic career ladder.